Involvement of SchRabGDI1 from Solanum chilense in endocytic trafficking and tolerance to salt stress. (October 2017) - Martín-Davison, Alex San; Pérez-Díaz, Ricardo; Soto, Flavia; Madrid-Espinoza, José; González-Villanueva, Enrique; Pizarro, Lorena; Norambuena, Lorena; Tapia, Jaime; Tajima, Hiromi; Blumwald, Eduardo; Ruiz-Lara, Simón
Highlights: We characterized the SchRabGDI1 a salt-induced gene in wild tomato species Solanum chilense . This gene encodes a functional GDP dissociation inhibitor, which showed to regulate the endocytic pathway. Arabidopsis thaliana expressing SchRabGDI1 showed increased salt tolerance. Abstract: Physiological responses of plants to salinity stress requires the coordinated activation of many genes. A salt-induced gene was isolated from roots of the wild tomato species Solanum chilense and named SchRabGDI1 because it encodes a protein with high identity to GDP dissociation inhibitors of plants. These proteins are regulators of the RabGTPase cycle that play key roles in intracellular vesicular trafficking. The expression pattern of SchRabGDI1 showed an early up–regulation in roots and leaves under salt stress. Functional activity of SchRabGDI1 was shown by restoring the defective phenotype of the yeast sec19-1 mutant and the capacity of SchRabGDI1 to interact with RabGTPase was demonstrated through BiFC assays. Expression of SchRabGDI 1 in Arabidopsis thaliana plants resulted in increased salt tolerance. Also, the root cells of transgenic plants showed higher rate of endocytosis under normal growth conditions and higher accumulation of sodium in vacuoles and small vesicular structures under salt stress than wild type. Our results suggest that in salt tolerant species such as S. chilense, bulk endocytosis is one of the early mechanisms to avoid salt stress, which requires the concerted expression of regulatory genes involved in vesicular trafficking of the endocytic pathway.